EFEK EDIBLE COATING PADA KUALITAS ALPOKAT (PERSEA AMERICA MILL ) SELAMA PENYIMPANAN - Nisah, Khairun (AMINA, 2019)
Research has been carried out entitled the effect of carrageenan addition Eucheuma cottonii and glycerol as edible coating of avocado fruit (Persea americana Mill.) From Takengon, Central Aceh Regency to extend storage time. This study aims to find out how the effect of the addition of carrageenan concentration variations Eucheuma cottonii and glycerol as edible coatings in extending the shelf life of avocados (Persea americana Mill.). The variations in the concentration of comparable carrageenan and glycerol used as edible coating are 2: 2%, 3: 2%, 4: 2%, 2: 3%, 3: 3% and 4: 3% in distilled water. The coating process is done by dipping avocados for 1 minute and stored at room temperature for 10 days in an open container. The results showed that the physical appearance of avocados was best obtained from edible coating with variations in concentrations of 2: 2%, 2: 3% and 3: 3% (carrageenan: glycerol) characterized by bright flesh color, hard texture, fresh aroma and good taste, while avocados at carrageenan concentrations and glycerol 3: 2%, 4: 2% and 4: 3% indicate poor conditions and are not suitable for consumption. Avocados with edible coating 2: 2%, 2: 3% and 3: 3% were then tested and obtained by weight loss in a row of 11.562%, 8.815% and 9.34%, moisture content 73.73%, 65.77% and 77.84%, reducing sugar levels 1.15%, 0.80% and 0.97% and vitamin C levels 0.17%, 0.16% and 0.31%.